2004
DOI: 10.1002/bjs.4389
|View full text |Cite
|
Sign up to set email alerts
|

Adverse histopathological findings as a guide to patient management after curative resection of node-positive colonic cancer

Abstract: Patients with a stage C tumour but with none of the identified adverse features experience relatively good survival and are unlikely to benefit from adjuvant chemotherapy. In this series such patients accounted for 40.5 per cent of patients with stage C disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…3,4 Another study has shown that patients with Stage III disease who are free of adverse prognostic factors, such as serosal surface involvement, apical node metastasis, high histologic grade, and venous invasion, have relatively good outcomes. 5 These studies were conceptually similar and indicate the importance of identifying patients with Stage II disease who are at high-risk, comparable with that in Stage III disease. Clinical trials have demonstrated that 5-fluorouracil (5-FU)/leucovorin improves survival in Stage III colorectal cancer, 2,6 but consensus has not been reached about the use of adjuvant chemotherapy in patients with Stage II disease whose prognosis is as poor as that in Stage III disease.…”
mentioning
confidence: 62%
“…3,4 Another study has shown that patients with Stage III disease who are free of adverse prognostic factors, such as serosal surface involvement, apical node metastasis, high histologic grade, and venous invasion, have relatively good outcomes. 5 These studies were conceptually similar and indicate the importance of identifying patients with Stage II disease who are at high-risk, comparable with that in Stage III disease. Clinical trials have demonstrated that 5-fluorouracil (5-FU)/leucovorin improves survival in Stage III colorectal cancer, 2,6 but consensus has not been reached about the use of adjuvant chemotherapy in patients with Stage II disease whose prognosis is as poor as that in Stage III disease.…”
mentioning
confidence: 62%
“…Although peritoneal involvement, the hallmark of pT4 disease, represents a well‐established prognostic parameter in colorectal cancer, a systemic study analysing the prognosis for patients with pT4a cancer (perforates visceral peritoneum) and pT4b cancer (directly invades other organ or structures) is still lacking 10–13. A recent retrospective study by Pollheimer et al showed that the pT4 sub‐classification, does not yield significant data about the patients' oncological outcomes (83% of patients with pT4a and 85% of patients with pT4b tumors experienced disease progression, P = 0.930) 14.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies analysing node-positive or stage III colorectal cancer, which, however, did not assess the prognostic impact of lymphatic invasion, also identified T classification (or serosal involvement),8–11 N classification (or number of positive lymph nodes)8–10 and poor tumour differentiation8 10 11 as independent predictors of poor outcome. In addition, lymph node ratio, venous invasion, tumour location, adjuvant chemotherapy and preoperative carcinoembryonic antigen (CEA) level have also been reported as significant prognosticators in this subgroup 8–11…”
Section: Discussionmentioning
confidence: 99%